Efficacy of autologous fibrin glue versus sutures in reducing astigmatism following pterygium surgery: A 1-year randomized controlled study - Sheetal Vishwanath Girimallanavar; Rekha Mudhol; Vijayalaxmi S Kori (Wolters Kluwer Medknow Publications, 2022)
AIM: To evaluate the astigmatic changes before and after pterygium surgery and to study the effect of autologous fibrin glue over sutures in terms of efficacy in reducing corneal astigmatism. SETTINGS AND DESIGN: Randomized controlled trial. SUBJECTS AND METHODS: Forty-four patients with primary pterygia were taken up and divided as follows: Conjunctival autograft with autologous fibrin glue as Group 1 (n = 22) and autograft with 8-0 vicryl sutures as Group 2 (n = 22). All patients were preoperatively assessed for visual acuity, anterior, posterior segments, and Keratometric values using Bausch-Lomb keratometer on postoperative day 1, 7, 1 month, and 3 months. STATISTICAL ANALYSIS: Mann-Whitney test was performed to compare the median keratometric astigmatic changes preoperatively and postoperatively between the groups. P < 0.05 was considered statistically significant. RESULTS: 50.5 was the mean age and 14.81 standard deviation (SD) in Group 1 and 48.86 was the mean and 13.23 SD in Group 2. Group 1 had 40.9% males and 59.1% females, Group 2 had 54.5% males and 45.5% females. The preoperative keratometric values significantly decreased postoperatively in both groups and the median postoperative keratometric value was significantly reduced in Group 1 (0.5) as compared to Group 2 (1.25). Pterygium excision using autologous blood was more effective in reducing corneal astigmatism. CONCLUSION: Pterygium excision surgery reduces corneal astigmatism and thus improves visual acuity. Autologous blood is better option to attach the conjunctival autograft than sutures in reducing astigmatism.